An Overview of Wireless Networks Towards Internet (International Journal of Innovative Research in Computer Science & Technology, 2022)
With advances in wireless technology  and digital electronics, several small gadgets have begun  to be utilized in a variety of everyday situations. The  concept of IoT enables rapid access to environmental data.  Efficiency and productivity are drastically increasing in  many operations. This paper provides a comprehensive  review of WSNs. These gadgets have the ability to sense,  compute, and communicate. Low-power radios, a number  of smart sensors, and embedded CPUs are common  components (Central Processing Units). These devices are  used to create a wireless sensor network (WSN), which is  required for detecting and monitoring environmental  variables. Parallel to WSNs, the concept of the internet of  things (IoT) is gaining traction, with IoT being defined as  the connectivity of identifiable objects via an internet  connection for sensing and monitoring purposes. This  article provides a comprehensive review of WSNs. It also  evaluates WSNs' technology and features. In addition, it  includes a discussion of WSN and IoT applications.
Keywords: Ad-hoc Network; Internet of Things (IoT; Sensor Node; Wireless Sensor Networks; WSN Security